TRAJECTORIES OF MUTUAL ZOMBIFICATION IN THE PRAXIS OF POST-COLONIAL FAITH IN SOUTH AFRICA: - B. Dube (Acta Theologica)
In this theoretical article, I tap into Mbembe’s (1992) concept of mutual zombification to start a debate on the need for African decoloniality theology (ADT) for a contemporary praxis of Christian faith. Observing the praxis of faith in post-colonial states among the “new” religious movements, I argue that there is a need for theologians to rethink theology in the context of religious mafiarisation, extortion, abuse, constitutional delinquency, political oppression and coloniality of God. I use decoloniality theory to articulate and suggest the need for ADT. I answer the question: What are the trajectories of mutual zombification and how will ADT involve? I submit that ADT can provide meaning to faith in post-colonial states that are devoid of coloniality, oppression, extortion, and constitutional delinquency, a Christian faith where people tap into both modernity and post-modernity, as opposed to mutual zombification that favours abusive religious leaders.